2018
DOI: 10.1523/eneuro.0367-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Zic4-Lineage Cells Increase Their Contribution to Visual Thalamic Nuclei during Murine Embryogenesis If They Are Homozygous or Heterozygous for Loss of Pax6 Function

Abstract: Our aim was to study the mechanisms that contribute to the development of discrete thalamic nuclei during mouse embryogenesis (both sexes included). We characterized the expression of the transcription factor coding gene Zic4 and the distribution of cells that expressed Zic4 in their lineage. We used genetic fate mapping to show that Zic4-lineage cells mainly contribute to a subset of thalamic nuclei, in particular the lateral geniculate nuclei (LGNs), which are crucial components of the visual pathway. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…3A,B). Zic4 is also expressed by some prethalamic cells, with an onset of expression similar to that of Gsx2 (about E9.5; Gaston-massuet et al, 2005), and most diencephalic Zic4 lineage cells express and require Pax6 for their normal development (Li et al, 2018). Using a Zic4 Cre line (Rubin et al, 2011), we observed that prethalamic neurons derived from Zic4 lineage were located in a narrow band close to the thalamic-prethalamic border (Fig.…”
Section: Loss Of Prethalamic Pioneer Axons Correlates With Abnormal Tmentioning
confidence: 82%
See 2 more Smart Citations
“…3A,B). Zic4 is also expressed by some prethalamic cells, with an onset of expression similar to that of Gsx2 (about E9.5; Gaston-massuet et al, 2005), and most diencephalic Zic4 lineage cells express and require Pax6 for their normal development (Li et al, 2018). Using a Zic4 Cre line (Rubin et al, 2011), we observed that prethalamic neurons derived from Zic4 lineage were located in a narrow band close to the thalamic-prethalamic border (Fig.…”
Section: Loss Of Prethalamic Pioneer Axons Correlates With Abnormal Tmentioning
confidence: 82%
“…We first assessed whether delayed ubiquitous Pax6 deletion, induced in CAG CreER-TM Pax6 fl/fl embryos (referred to here as CAG CreER Pax6 cKOs), disrupts the topography of TCA connections. We induced Cre recombinase activation by tamoxifen administration at E9.5, which caused Pax6 protein loss in CAG CreER Pax6 cKOs from E11.5 onwards (Quintana-Urzainqui et al, 2018), which is when the generation of most thalamic neurons is starting (Li et al, 2018) and before many TCAs have begun to grow (Auladell et al, 2000;López-Bendito and Molnár, 2003). Diencephalic progenitor domains in CAG CreER Pax6 cKOs are fully recognizable (Quintana-Urzainqui Fig.…”
Section: Thalamocortical Topography Is Disrupted In Cag Creer But Notmentioning
confidence: 99%
See 1 more Smart Citation
“…We first assessed whether delayed ubiquitous Pax6 deletion, induced in CAG CreER-TM Pax6 fl/fl embryos (referred to here as CAG CreER Pax6 cKOs), disrupts the topography of TCA connections. We induced Cre recombinase activation by tamoxifen administration at E9.5 which caused Pax6 protein loss in CAG CreER Pax6 cKOs from E11.5 onwards (Quintana-Urzainqui et al, 2018), which is when the generation of most thalamic neurons is starting (Li et al, 2018) and before many TCAs have begun to grow (Auladell and Hans, 2000; López-Bendito and Molnár, 2003). We used both wild type and CAG CreER Pax6 fl/+ littermate embryos as controls since the latter express normal levels of Pax6 protein, almost certainly because of a feedback loop that compensates for a deletion in one allele by increasing the activity of the other (Caballero et al, 2014; Manuel et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The maintenance of order among thalamic axons as they grow is likely to contribute to the generation of orderly topographic mapping in the mature thalamocortical tract. During embryogenesis, thalamic axons exit the thalamus from about E12.5 onwards (Auladell and Hans, 2000; Braisted et al, 1999; Tuttle et al, 1999), approximately coincident with the cessation of neurogenesis in this structure (Angevine, 1970; Li et al, 2018). They then cross the adjacent prethalamus and turn laterally out of the diencephalon and into the ventral telencephalon where they traverse two consecutive instructive regions - the corridor (Lopez-Bendito et al, 2006) and the striatum - before entering the cortex.…”
Section: Introductionmentioning
confidence: 99%